Answer:
4) 6x - y = 11
5) x + y = 7
6) 9x - y = - 47
Step-by-step explanation:
4) the slope of the equation is 6 and it passes through the point (3,7).
Therefore, the equation of the straight line is y = 6x + c {Where c is a constant}
Now, putting x = 3 and y = 7, in the above equation we get, c = 7 - 18 = - 11
Therefore, the equation is y = 6x - 11
⇒ 6x - y = 11 (Answer)
5) the slope of the equation is -1 and it passes through the point (2,5).
Therefore, the equation of the straight line is y = - x + c {Where c is a constant}
Now, putting x = 2 and y = 5, in the above equation we get, c = 5 + 2 = 7
Therefore, the equation is y = - x + 7
⇒ x + y = 7 (Answer)
6) the slope of the equation is 9 and it passes through the point (-5,2).
Therefore, the equation of the straight line is y = 9x + c {Where c is a constant}
Now, putting x = - 5 and y = 2, in the above equation we get, c = 2 + 45 = 47
Therefore, the equation is y = 9x + 47
⇒ 9x - y = - 47 (Answer)